Identifying and prioritizing components and indicators of educational inequality in elementary schools - moslem piri zamaneh; Abass Abasspuor; Hamid Rahimian (Pizhūhish/hā-yi rahbarī va mudīriyyat-i āmūzishī, 2023)
This research was conducted with the aim of identifying and prioritizing indicators of educational inequality in primary schools in Tehran and it is an exploratory type of research. The statistical population under investigation is all public elementary schools in Tehran. The statistical sample in the qualitative section includes 14 experts and experts in the field of public education, who were selected by snowball sampling, and in the quantitative section, principals, assistants and experts of primary schools in Tehran, who were selected in a multi-stage cluster. . Data collection tools include semi-structured interview, researcher made checklist. The results showed that the educational inequality at the level of primary schools in Tehran includes 7 components, 28 indicators, which are: input component including 4 indicators, school process component including 6 indicators, family background component including 6 indicators, output component including 8 Index, individual context of inequality including 4 indicators, social and political effects of inequalities in education including 4 indicators, geographical indicators. Also, in terms of the influence of components and indicators The amount of benefit from education, and the next priorities in the order of human resources (good teachers), family cultural capital, students' educational aspirations, small family population, school management, parents' expectations and aspirations, parents' educational status, educational progress , the acceptance status of students in model schools, sports, cultural and scientific authorities, the handling of educational trustees, the education of descent, the level of attention of teachers to students, attention to the quality of education.